THE IMPACT OF PHYSICAL THERAPY ON THE CONDITION OF PATIENTS WITH COVID-19 DURING LONG-TERM REHABILITATION - Korota , Yu. V.; Nekhanevych, O. B. (Rehabilitation and Recreation, 2023)
To evaluate the impact of physical therapy on the quality of life and cardiorespiratory endurance of COVID-19 patients during long-term rehabilitation. The study involved 60 patients (average age 59(8.3) years) who were hospitalized due to COVID-19. Patients were randomly assigned to two groups, with 30 individuals in each: the intervention group and the control group. The intervention group received a physical therapy program, which included exercises to improve lower limb strength, activities to restore physical endurance, stretching exercises for trunk, chest, and upper limb muscles, exercises aimed at enhancing respiratory muscle strength, controlled breathing, and airway clearance during the first 6 weeks post-discharge. All patients underwent surveys, anthropometry, assessments of quality of life using the SF-36 questionnaire, and cardiorespiratory endurance using the 6-minute walk test. A positive impact of the physical rehabilitation course was observed after 6 weeks concerning the quality of life indicators: physical functioning (57(17.3) vs. 46.8 (14.8)), vitality (56.7(9.2) vs. 47.7(7.7)), and general health status (55.3(7.1) vs. 49(4.9)), respectively (p < 0.05). The statistically significant difference between the intervention and control groups persisted at 12 months for vitality (61.5(7.4) vs. 57.3(6.8)) and mental health (59.7(9.4) vs. 54.1(8.5)), respectively (p < 0.05). The 6-minute walk test values were significantly higher in the intervention group immediately after 6 weeks of rehabilitation (413(76.8) m vs. 342.8(73.0) m, respectively; p < 0.05). This statistically significant difference between the groups persisted over the course of the year. The application of physical therapy for COVID-19 patients during the first 6 weeks post-discharge positively influences their quality of life, specifically enhancing physical functioning, mental health, and vitality, and this improvement is maintained up to 12 months compared to patients who did not receive physical therapy. Patients who underwent physical therapy also demonstrated higher cardiorespiratory endurance from the 6th week onwards, and this improvement was sustained throughout the year.